Non-mosaic trisomy 22 and congenital heart surgery using the shared decision making model: a case report - Vivien Phung; Kathryn E. Singh; Saar Danon; Christopher A. Tan; Sarah Dabagh (BMC, 2023)
Abstract Background Liveborn infants with non-mosaic trisomy 22 are rarely described in the medical literature. Reported lifespan of these patients ranges from minutes to 3 years, with the absence of cardiac anomalies associated with longer-term survival. The landscape for offering cardiac surgery to patients with rare autosomal trisomies is currently evolving, as has been demonstrated recently in trisomies 13 and 18. However, limited available data on patients with rare autosomal trisomies provides a significant challenge in perinatal counseling, especially when there are options for surgical intervention. Case presentation In this case report, we describe an infant born at term with prenatally diagnosed apparently non-mosaic trisomy 22 and multiple cardiac anomalies, including a double outlet right ventricle, hypoplastic aortic valve and severe aortic arch hypoplasia, who underwent cardiac surgery. The decisions made by her family lending to her progress and survival to this day were made with a focus on the shared decision making model and support in the prenatal and perinatal period. We also review the published data on survival and quality of life after cardiac surgery in infants with rare trisomies. Conclusions This patient is the only known case of apparently non-mosaic trisomy 22 in the literature who has undergone cardiac surgery with significant survival benefit. This case highlights the impact of using a shared decision making model when there is prognostic uncertainty.